Quality of life of covid-19 patients attending selected post-covid units - Rahman, Md Raziur; Akhtar, Khursheda; Azizi, Shajeda; Nurunnabi, Mohammad; Chowdhury, Monzur Al Morshed; Adnan, Md Asif (Journal of Preventive and Social Medicine, 2024)
Background: Disease process and its outcome can create impacts on human life; it also impairs quality of life (QoL). During the COVID-19 pandemic situation, a devastating impairment of quality of human life has been occurred over the world. This study aimed to state the quality of life of COVID-19 patients attending post-COVID units of Dhaka Medical College Hospital and Bangabandhu Sheikh Mujib Medical University, Dhaka. Methods: A cross-sectional study was conducted among 90 COVID-19 Patients (post-COVID period) in post COVID unit of Dhaka Medical College Hospital and Bangabandhu Sheikh Mujib Medical University by pretested structured questionnaire, from July 2021 to December 2021, using a convenient sampling method. Data were collected through face-to-face interviews. Results: The majority of the respondents (46.7%) were within the 30 to 39 years of age group. In this study about 73.3% of respondents lead poor quality of life after recovery from COVID-19. The findings revealed that, Post COVID depression history of the respondents was associated with the quality of life of the respondents after recovery from COVID-19 (p=0.001). The findings also revealed that the type family of the respondents was associated with the quality of life of the respondents after recovery from COVID-19 (p=0.001). Those who were not admitted into hospital during COVID-19 period maintain good quality of life after recovery from COVID-19 than those who were admitted on hospital during COVID-19 period (p=0.006). Inferential statistics were done at a 95% confidence interval and 5% level of significance. Conclusions: This study described state of quality of life of COVID-19 patients attending on post-COVID units. It was found that near about three fourth of the respondents seemed that their quality of life became poor after recovery from COVID-19. JOPSOM 2023; 42(1):49-53